Burden of pulmonary tuberculosis and challenges related to tuberculosis detection in Ethiopia - Letebrhan Weldemhret (Journal of Infection in Developing Countries)
Early and rapid diagnosis of Mycobacterium tuberculosis in clinical specimen is important for the treatment of patients and control of disease transmission to the community. The disease is largely preventable and curable, but without rapid, and correct diagnostic tools for tuberculosis (TB) infection and drug resistance, it is unlikely that we can meet the national TB elimination program in Ethiopia by 2035. Moreover, drug resistant TB is becoming more common and is a great challenge for the successful control and eradication of TB. The need for rapid, accurate and affordable methods for TB management should be considered by policy makers to improve TB detection rate and reduction of TB related deaths in line with the stop TB strategy by 2030 in Ethiopia.